A Problem with Condition Containing an Integral Term for a Parabolic-Hyperbolic Equation - Kuz, A. M.; Ptashnik, B. I.; Кузь, А. М.; Пташник, Б. Й. (Institute of Mathematics, NAS of Ukraine, 2015)
In a layer obtained as the Cartesian product of an interval $[−T_1 ,T_2], T_1 ,T_2 > 0$, and a space $ℝ_p, p ≥ 1$, we study a problem with nonlocal condition in the time variable containing an integral term for a mixed parabolic-hyperbolic equation in the class of functions almost periodic in the space variables. For this problem, we establish a criterion of uniqueness and sufficient conditions for the existence of solutions. To solve the problem of small denominators encountered in the construction of the solution, we use the metric approach.